Blue LED Induced Manganese (I) Catalysed Direct C2−H Activation of Pyrroles with Aryl Diazoesters. Issue 14 (31st May 2021) - Sar, Saibal; Das, Ranajit; Sen, Subhabrata
Abstract: Herein, we have reported a blue LED mediated manganese pentacarbonyl bromide catalysed incorporation of carbene moieties from aryl diazoesters onto 1H‐pyrroles via their selective C2−H activation. A manganese metal‐carbene has been identified as the active catalyst to facilitate the reaction. Eighteen mono substituted pyrrole derivatives were isolated in good to excellent yields (67→82%) and the disubstituted products were also formed in minor quantities (5 to 8%). HPLC based kinetics study enabled optimization of the reaction. Control experiments, FT‐IR, NMR and GC‐MS based characterization elucidated the putative reaction mechanism. Abstract :